2015
DOI: 10.1364/oe.23.031384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fresnel reflections in a hybrid air-core photonic-bandgap fiber ring-resonator gyro

Abstract: A novel hybrid polarization-maintaining (PM) air-core photonic bandgap fiber (PBF) ring resonator is firstly demonstrated by using a conventional solid-core PM fiber optical coupler formed by splicing a section of PM air-core PBF into the resonator. Due to Fresnel reflections exist at the two junctions between the air-core PBF and the solid-core fiber, the forward output signal of this hybrid ring resonator is the normal resonant curve with the superposition of the lightwaves that experienced even numbers of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…By using a polarization maintaining HC-PBGF and a hybrid solid/hollow resonator, Yan et al improved this to 25 deg/hr stability [2] at τ≈0. 1 hr [11]. More recently, Suo et al [2] demonstrated the beneficial aspects of anti-resonant guiding HCF, showing 0.…”
Section: Introductionmentioning
confidence: 98%
“…By using a polarization maintaining HC-PBGF and a hybrid solid/hollow resonator, Yan et al improved this to 25 deg/hr stability [2] at τ≈0. 1 hr [11]. More recently, Suo et al [2] demonstrated the beneficial aspects of anti-resonant guiding HCF, showing 0.…”
Section: Introductionmentioning
confidence: 98%
“…They exhibit high fiber splicing loss when fusing with glass-core fibers. 8 Kristensen et al studied the fusion splicing between PMF and hollow-core fiber, and the fusion loss reached 0.62 ± 0.24 dB, but it is still a stochastic process, and the strength of the fusion point between hollow-core fiber and PMF is usually very fragile. 9 In addition, nested antiresonant nodeless fiber (NANF) has been significantly developed this year, and transmission loss reached 1.3 dB/km.…”
Section: Introductionmentioning
confidence: 99%
“…However, HCPCFs are not compatible with conventional fiber couplers. They exhibit high fiber splicing loss when fusing with glass‐core fibers 8 . Kristensen et al studied the fusion splicing between PMF and hollow‐core fiber, and the fusion loss reached 0.62 ± 0.24 dB, but it is still a stochastic process, and the strength of the fusion point between hollow‐core fiber and PMF is usually very fragile 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The generation of multiple-frequency lasers with low relative phase noise and radio wavelength frequency differences is the key requirement for the differential detection scheme [7,8]. For HC-RFOGs, the required frequency differences between the lasers are usually only in the order of tens of MHz [9][10][11].…”
Section: Introductionmentioning
confidence: 99%